Matthew's story : from sinner to saint - LaHaye, Tim F.; Jenkins, Jerry B. (New York : Berkley Praise, 2011)
Portrays the story of how Levi the tax collector became Matthew, the apostle of Jesus Christ and one of the great authors of the Gospels.
Keywords: Matthew, -- the Apostle, Saint -- Fiction; Bible. -- History of Biblical events -- Fiction